It's Christmas, David! - Shannon, David, 1959- (New York : Blue Sky Press, 2010)
Christmas has arrived with so many rules to follow that David fears his mistakes will cause Santa to pass him by.
0.9
K-3
K-3.
AD300L
Keywords: Christmas -- Juvenile fiction; Human behavior -- Juvenile fiction; Santa Claus -- Juvenile fiction; Christmas -- Fiction; Behavior -- Fiction; Santa Claus -- Fiction; Christmas -- Fiction; Human behavior -- Fiction; Santa Claus -- Fiction; Picture books for children